Theoretical aspects of gas turbine combustion performance - Lefebvre, Arthur H. (College of Aeronautics, 1966)
A correlating parameter for gas turbine combustion performance, based on a 'burning velocity' theory for primary zone combustion is derived using a more direct approach than that originally employed by Greenhough and Levebvre.1 The various applications of this parameter are discussed and it is shown that the shape of correlated performance curves is directly related to the combustion processes taking place in the various zones of the chamber. An alternative, more basic, theory is presented in which it is assumed that the low-pressure performance of a spray-type combustor is controlled by a balance between the separate effects of chemical reaction, fuel evaporation and mixing. It is argued that combustion efficiency is a function of p2 /M where x = 2.0, 1.7 or 1.0 depending upon whether the rate of heat release is governed by chemical reaction, fuel evaporation or mixing respectively. It is postulated that the amount by which values of x determined experimentally fall below 1.7 provides a useful practical indication of the extent to which mixing is intervening in the overall combustion process. At high pressures the mixing process predominates, x = 1, and it is shown that, for any given fuel-air ratio, the rate of heat release depends only on flame-tube geometry and mode of fuel injection, and is independent of chamber size, pressure loss factor and the operating conditions of pressure, temperature and velocity. The basic principles involved in the design of primary combustion zones for maximum volumetric heat release rate and maximum stability in terms of wide burning range are discussed.